2011
DOI: 10.4049/jimmunol.1002146
|View full text |Cite
|
Sign up to set email alerts
|

CD23-Dependent Transcytosis of IgE and Immune Complex across the Polarized Human Respiratory Epithelial Cells

Abstract: IgE-mediated allergic inflammation occurs when allergens cross-link IgE on the surface of immune cells, thereby triggering the release of inflammatory mediators as well as enhancing Ag presentations. IgE is frequently present in airway secretions, and its level can be enhanced in human patients with allergic rhinitis and bronchial asthma. However, it remains completely unknown how IgE appears in the airway secretions. In this study, we show that CD23 (FcεRII) is constitutively expressed in established or prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 66 publications
4
70
0
1
Order By: Relevance
“…The interaction between IgE and CD23 is critically involved in the allergic response at several stages, including allergen presentation, the regulation of IgE synthesis, and transport of IgE and immune complexes across epithelial barriers in the gut and airways (1,14,15,17,18). At the cell surface, mCD23 is trimeric (9,31,32), and sCD23 fragments shed from the membrane that contain sufficient stalk region are also trimeric (31), although the structure of the trimer has only been modeled either on the basis of the structures of other C-type lectins (25) or guided by NMR chemical shift data (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between IgE and CD23 is critically involved in the allergic response at several stages, including allergen presentation, the regulation of IgE synthesis, and transport of IgE and immune complexes across epithelial barriers in the gut and airways (1,14,15,17,18). At the cell surface, mCD23 is trimeric (9,31,32), and sCD23 fragments shed from the membrane that contain sufficient stalk region are also trimeric (31), although the structure of the trimer has only been modeled either on the basis of the structures of other C-type lectins (25) or guided by NMR chemical shift data (6).…”
Section: Discussionmentioning
confidence: 99%
“…CD23 expressed on B cells also has the potential to contribute to the clinically serious phenomenon of the spreading of allergic reactivity to unrelated allergens, through its ability to internalize IgE-allergen complexes irrespective of the allergen, in contrast to mIgE-mediated allergen-specific presentation through the B-cell receptor (1). CD23 expressed on gastrointestinal epithelial cells also contributes to IgE-allergen transport across the gut epithelial barrier to trigger food allergenic reactions (17) and similarly on respiratory tract epithelial cells to contribute to airway allergic inflammation (18). Understanding the IgE-CD23 interaction thus has implications for many aspects of allergic disease.…”
mentioning
confidence: 99%
“…It is expressed mainly on B-cells, and regulates IgE production as well as B-cell differentiation, antigen presentation through CD23-MHC II [18,25] and interactions with epithelial cells [26]. IgE only binds CD23 when complexed to an allergen by formation of a trimolecular complex.…”
Section: Role Of Ige and Its Receptorsmentioning
confidence: 99%
“…The lowaffinity IgE receptor FcεRII, also known as CD23, appears to play a role in the transcytosis of IgE and IgE-containing immune complexes across the epithelium at mucosal surfaces. FcεRII has been shown to be capable of bidirectional transport of IgE across epithelial cells in vitro (Tu et al, 2005) and its expression has been demonstrated on human intestinal cells and airway epithelial cells, as well as related cell lines (Tu et al, 2005;Li et al, 2006;Palaniyandi et al, 2011). The evidence suggests that FcεRII may transcytose IgE and associated antigens/allergens across the mucosal epithelial barrier and thereby contribute to intestinal and airway allergy and modulation of infection.…”
Section: Fcr-mediated Ige Activity In Mucosal Secretionsmentioning
confidence: 92%